Investigation of Vaspin Level in Patients with Acute Ischemic Stroke - Cura, Hasan S.; Ozdemir, Hasan H.; Demir, Caner F.; Bulut, Serpil; Ilhan, Nevin; Inci, Mehmet Fatih (Elsevier, 2014)
Background: Cerebrovascular event is a clinical condition characterized by symptoms and findings pertaining to loss of focal cerebral function because of the vascular causes. Atherosclerosis has a forefront role in the pathogenesis of stroke. Inflammation has an important place in the formation of atherogenesis and atherosclerosis. Visceral adipose tissue-derived serpin (vaspin) is a new adipokine, which is identified recently, associated with obesity and diabetes and also has a proinflammatory characteristic. This study was intended to investigate the relation between vaspin and stroke and stroke and other risk factors. Methods: A total of 50 patients with stroke, as 28 men (56%) and 22 women (44%), and a total of 50 healthy individuals, as 25 men (50%) and 25 women (50%), were enrolled in the study. Blood samples were taken in the acute period (first 48 hours) in the patient group, and serumvaspin levels were measured. Vaspin level was also measured in the control group. The association of vaspin with the lipid parameters, gender, and the severity of internal carotid artery (ICA) stenosis in the patient group was evaluated. Stenotic plaques in ICA were classified as normal, mild (stenosis under 50%), moderate (stenosis 50%-69%), severe (stenosis 70%-99% to preocclusion), and occlusion. Results: No statistically significant difference was found between 2 groups in terms of age and gender (P > .05). Vaspin levels were found to be significantly higher in the patient group (164.73 +/- 153.76 ng/mL) compared with the control group (116.21 +/- 34.60 ng/mL) (P < .05). However, no relation was established between vaspin level and the severity of ICA stenosis. Conclusions: Vaspin levels have been shown to increase in acute ischemic stroke patients. The increased vaspin levels may vary depending on several factors in acute period of ischemic stroke.
Keywords: Vaspin; ischemic stroke; carotid artery stenosis; cerebrovascular event; carotid artery ultrasound